The Bathsheba Syndrome: The ethical failure of successful leaders - Ludwig, Dean C. (Journal of business ethics, 1993)
Reports of ethical violations by upper level managers continue to multiply despite increasing attention being given to ethics by firms and business schools. Much of the analysis of these violations focuses on either these managers'lack of operational principles or their willingness to abandon principles in the face ofcompetitive pressures. Much of the attention by firms and business schools focuses either on the articulation of operational principles (a deontological approach) or on the training of managers to sort their way through subtle ethical dilemmas in the face of competitive pressure (a utilitarian approach). While valuable, these approaches alone are incomplete., This paper suggests that many ethical violations by upper managers are the by-product ofsuccess — not of competitive pressures. Our research suggests that many managers are poorly prepared to deal with success. First, success often allows managers to becomecomplacent and to lose focus, diverting attention to things other than the management of their business. Second, success, whether personal or organizational, often leads toprivileged access to information, people or objects. Third, with success usually comes increasinglyunrestrained control of organizational resources. And fourth, success can inflate a manager's belief in his or her personalability to manipulate outcomes. Even individuals with a highly developed moral sense can be challenged (tempted?) by the “opportunities” resulting from the convergence of these dynamics. We label the inability to cope with and respond to the by-products of success “the Bathsheba Syndrome,” based on the account of the good King David (a story familiar in a variety of traditions). Recognition of this phenomenon implies that we change or broaden our approach to the teaching of business ethics. It also implies that organizations must re-evaluate and change structures, procedures, and practices which enhance the likelihood of managers falling victim to the Bathsheba Syndrome.